2011
DOI: 10.1007/s12011-011-9002-4
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Chromium(III) Picolinate for Reproductive or Developmental Toxicity Following Exposure of Male CD-1 Mice Prior to Mating

Abstract: Chromium(III) picolinate, [Cr(pic)(3)], is a commonly used nutritional supplement in humans, which has also been approved for use in animals. Health concerns have arisen over the use of [Cr(pic)(3)]. At high [Cr(pic)(3)] doses, developmental toxicity tests in female mice have shown a higher litter incidence of split cervical arch in exposed fetuses, but this was not consistently reproducible. In the current study, male CD-1 mice were used to further assess the potential for reproductive or developmental toxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…per day (25 mg Cr(III)/kg b.w. per day) before mating had no effect on fertility, prenatal mortality, fetal weight or skeletal morphology (McAdory et al, 2011).…”
Section: Developmental and Reproductive Toxicitymentioning
confidence: 86%
“…per day (25 mg Cr(III)/kg b.w. per day) before mating had no effect on fertility, prenatal mortality, fetal weight or skeletal morphology (McAdory et al, 2011).…”
Section: Developmental and Reproductive Toxicitymentioning
confidence: 86%
“…Bailey (2006) reported increased incidence of bifurcated arches, McAdory et al (2011) observed an increase in the number of resorbed or dead foetuses and Bailey et al (2008) did not observe any maternal or fetal toxicity. Bailey (2006) reported increased incidence of bifurcated arches, McAdory et al (2011) observed an increase in the number of resorbed or dead foetuses and Bailey et al (2008) did not observe any maternal or fetal toxicity.…”
Section: Developmental Toxicitymentioning
confidence: 87%
“…Thus, the mechanism by which trivalent chromium has an effect upon body compositions is still unclear [33,40,47,48]. It also should be mentioned that safety regarding the intake of chromium picolinate has not been established [49]. Many authors hold the opinion that chromium may reduce body mass by a number of mechanisms.…”
Section: Discussionmentioning
confidence: 99%